Effects of moisture content on the strength of tropically weathered granite from Malaysia - Mohamad, Edy Tonnizam (Springer Verlag, 2016)
The strength of rock is significantly affected by weathering and moisture content. Due to climate conditions in the tropics, rock is weathered significantly and produces a thick weathering profile. Designing structures in rock with varying degrees of weathering creates problems due to varying material properties. This study was carried out to investigate the effects of moisture content on weathered Malaysian granite of various grades, focusing on strength which is an essential parameter in designing engineering rock structures. Weathering identification tests, Schmidt hammer tests, and impact index tests were performed at the site as part of the field study. In the laboratory, samples were analyzed for durability, point load index, moisture content, density, and X-ray diffraction (XRD), and underwent petrographic analysis to examine the mi neralogy. The results revealed that the degree of feldspars weathering and the amount of clay minerals are good weathering grade identifiers. The amount of fresh feldspar decreased from 72 % in grade I specimens to 0 % in grade V specimens, with an increase of altered feldspar and clay minerals fr om 0 to 60 %. The presence of feldspar and mica minerals above 1 % tended to increase the susceptibility of rock to the influence of water. It was also found that the reduction in strength becomes great er with an increasing weathering grade. In addition, the discolouration of rock material from greyish to brownish red also can be a good indicator of strength reduction due to moisture content. Based on the re sults, the extent of strength reduction depends upon the weathering grade, petrographic constituents and duration of water immersion.